2011
DOI: 10.3892/ijo.2011.1043
|View full text |Cite
|
Sign up to set email alerts
|

miR-185 and miR-133b deregulation is associated with overall survival and metastasis in colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) is one of the most common and deadly forms of cancer. Despite improved treatment modalities, post-operative recurrence and metastasis remain the major problems for extending patient survival after surgery. This highlights the need to search for biomarkers for prognostication and treatment stratification of colorectal cancer patients. In this study, we applied the SYBR-green quantitative PCR-based array approach to screen for differentially expressed miRNAs between patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 32 publications
3
90
0
Order By: Relevance
“…15 Recent studies have reported that miR-133b, mapped on chromosome 6p12.2, was downregulated in carcinomas in the urinary bladder, colon, lung and esophagus. [18][19][20][21] Downregulation of miR-133b in cancer cells seems to result in upregulation of target mRNA and thus, overexpression or activation of oncoprotein. In lung cancer, downregulation of miR-133b is correlated with upregulation of MCL-1 and BCL2L2, suggesting an anti-apoptotic role.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recent studies have reported that miR-133b, mapped on chromosome 6p12.2, was downregulated in carcinomas in the urinary bladder, colon, lung and esophagus. [18][19][20][21] Downregulation of miR-133b in cancer cells seems to result in upregulation of target mRNA and thus, overexpression or activation of oncoprotein. In lung cancer, downregulation of miR-133b is correlated with upregulation of MCL-1 and BCL2L2, suggesting an anti-apoptotic role.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of miR-1/-133a is associated with t(14;16) translocation multiple myeloma [152] , whilst reduced expression is associated with prostate cancer [102] and RCC [138] , respectively. Reduced expression of other myomiR combinations is also associated with TSCC [111] , ESCC [132] , HNSCC [114,143] , GIST [281] , bladder cancer (TCC) [93] , lung cancer [85,99] , colorectal cancer [86,87] and rhabdomyosarcoma [88] . downregulated and upregulated myomiRs respectively, and Table 6 lists validated myomiR targets related to enhanced cancer progression.…”
Section: Myomirs and Cancermentioning
confidence: 99%
“…downregulated and upregulated myomiRs respectively, and Table 6 lists validated myomiR targets related to enhanced cancer progression. An excellent review by Nohata et al [84] (2012) reported changes in the expression of the miR1/ 133a and miR206/133b cistron clusters in numerous cancers, typically finding reduced expression of different combinations of myomiRs, such as in lung cancer [85] , colorectal cancer [86,87] , rhabdomyosarcoma [88,89] , chordoma [90] osteosarcoma [91] , muscleinvasive bladder cancer [92] , bladder cancer (transitional cell carcinoma) (TCC) [93] , ESCC [94] , breast cancer [95] and prostate cancer [9597] . In different cancers (Figure 3) deregulation typically involves downregulation of one or more myomiR isomers, indicating they normally function as tumor suppressors in the tissues, limiting Metastatic CRC [301] Notch3, Hes1, Bcl-2 and MMP-9; Exogenous upregulation of miR-206 expression;…”
Section: Myomirs and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Akçakaya et al. 11 found that combination of upregulation of miR‐185 and downregulation of miR‐133b could predict poor survival and higher metastatic probability. Recent study by Nofech‐Mozes et al.…”
Section: Introductionmentioning
confidence: 99%